A fatigue life estimation algorithm based on Statistical Energy Analysis in high-frequency random processes - Wang, Yongyan; Chen, Haibo; Zhou, Hongwei (International journal of fatigue, 2016)
•A fatigue life estimation algorithm based on SEA is proposed.•The fatigue damage is not sensitive to stress PSD shapes in 1/3 octave band.•The stress RMS is enough to predict fatigue life in the proposed algorithm. A frequency-domain fatigue life estimation algorithm based on Statistical Energy Analysis (SEA) is proposed in this study for a structure subject to high-frequency loading. The main contribution is to observe that, when evaluated at 1/3-octave bands, the RMS value of the power spectral density (PSD) function is sufficiently refined to produce meaningful fatigue life estimates. A practical application concerning the fatigue life of a plate of aircraft subject to high-frequency random loading is presented to confirm the applicability of the proposed algorithm.